Victims Themselves of a Close Encounter: On the Sensory Language and Bass Fiction of Space Ape (In Memoriam) - tobias c. van Veen (Dancecult: Journal of Electronic Dance Music Culture, 2015)
This text is written in memoriam to dubstep emcee and poet Space Ape (Stephen Samuel Gordon, b. June 17th, 1970; d. October 2nd, 2014). By his own words, Space Ape arose from the depths of the black Atlantic, on a mission to relieve the “pressure” through bass fiction. My aim is to explicate Space Ape’s bass fiction as the intersection of material and imaginal forces, connecting it to a broader Afrofuturist constellation of mythopoetic becomings. Memory and matter converge in the affect and sounding of Space Ape the “hostile alien” (“Space Ape”, Burial, 2006), a figure shaped at the intersection of the dread body, riddim warfare, and speculative lyricism. Space Ape set out to “xorcise” that which consumed him from within by embracing the “spirit of change”. Turning to process philosophy, I demonstrate how Space Ape’s bass fiction—his virtual body—activates the abstract concepts of becoming in the “close encounter” with the hostile alien.